Predominance of M1UK type strains and their clinical associations in invasive Streptococcus pyogenes infections in Japan, 2023–2025 - Shigeo Hanada; Misako Takata; Miyuki Baba-Morozumi; Junichi Sasaki; Satoshi Iwata; Shigeki Nakamura; Kimiko Ubukata (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose The clinical relevance of M1 UK type strains of Streptococcus pyogenes in Japan remains insufficiently defined. We investigated the molecular epidemiology of M1 UK type strains and evaluated their clinical associations among adults with invasive group A Streptococcus (iGAS) infections. Methods We conducted a nationwide multicenter surveillance study of iGAS infections from December 2023 to March 2025. Molecular typing, profiling of M1 UK -associated single-nucleotide polymorphisms (SNPs) in the rofA , gldA , and pstB regions, and emm -cluster assignment were performed. Adult clinical characteristics and outcomes were compared between M1 UK type and non-M1 type infections after exclusion of the single adult M1 global case. Results Among 155 patients in the molecular epidemiology cohort, M1 UK type strains accounted for 58 isolates, whereas only one M1 global isolate was identified. Historical analysis showed that M1 global predominated among isolates collected in the early 2010s, whereas M1 UK type strains were detected mainly in recent periods. In adult clinical comparisons, M1 UK type infection was associated with streptococcal toxic shock syndrome (STSS; p = 0.004) and necrotizing fasciitis ( p < 0.001). In multivariable analysis, younger age, necrotizing fasciitis, and serum creatinine ≥ 2.0 mg/dL were associated with M1 UK type infection. Conclusion M1 UK type strains were important contributors to contemporary iGAS infections in Japan and were associated with severe clinical presentations, supporting sustained molecular surveillance beyond conventional emm typing.

Seasonal variation in bacterial community composition in the brackish meromictic Lake Suigetsu - Takafumi Kataoka; Yuki Sato-Takabe.; Yunosuke Nakamura; Takuhei Shiozaki; Yuya Tsukamoto; Satoshi Hanada (Antonie van Leeuwenhoek, 2026)

Additional biomarkers and emm types associated with group A streptococcal toxic shock syndrome: a Japanese nationwide observational study - Shigeo Hanada; Takeaki Wajima; Misako Takata; Miyuki Morozumi; Yukio Sato; Junichi Sasaki; Satoshi Iwata; Kimiko Ubukata (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Clinical manifestations and biomarkers to predict mortality risk in adults with invasive Streptococcus dysgalactiae subsp. equisimilis infections - Shigeo Hanada; Takeaki Wajima; Misako Takata; Miyuki Morozumi; Michi Shoji; Satoshi Iwata; Kimiko Ubukata (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The incidence of invasive Streptococcus dysgalactiae subsp. equisimilis (iSDSE) infections is increasing in developed countries, but studies on the risk factors for death in iSDSE infections are scant. Here, we aimed to clarify risk factors and predictors of mortality in adults with iSDSE infections. Methods A multicentre observational study of adults with iSDSE infections was conducted to investigate the effects of host factors, disease severity, biomarkers, and antibiotic regimens, and bacterial factors on 28-day mortality. Results The overall mortality rate of 588 patients was 10.4%, with a significant increase in those aged ≥ 60 years. Most of the patients (97.4%) had underlying diseases. The mortality rate (70.4%) of patients with severe disease was significantly higher than that of patients with mild-to-moderate disease (4.3%; p < 0.001). The risk factors for death identified using multivariable analysis were age ≥ 60 years (hazard ratio [HR], 3.4; 95% confidence interval [CI], 1.0–11.3, p = 0.042); severe disease (HR, 15.0; 95% CI 7.7–29.2, p < 0.001); bacteraemia without primary focus (HR, 20.5; 95% CI 2.8–152.3, p = 0.003); serum creatinine ≥ 2.0 mg/dL (HR, 2.2; 95% CI 1.2–4.0, p = 0.010); serum creatine kinase ≥ 300 IU/L (HR, 2.1; 95% CI 1.1–3.8, p = 0.019); and macrolide resistance (HR, 1.8; 95% CI 1.0–3.3, p = 0.048). Treatment regimens and emm types were not associated with poor outcomes. Conclusion Evaluation of clinical manifestations and biomarkers on admission is important to predict invasive SDSE infection prognosis.

Neotabrizicola shimadae gen. nov., sp. nov., an aerobic anoxygenic phototrophic bacterium harbouring photosynthetic genes in the family Rhodobacteraceae, isolated from a terrestrial hot spring - So Muramatsu; Setsuko Hirose; Takao Iino; Moriya Ohkuma; Satoshi Hanada; Shin Haruta (Antonie van Leeuwenhoek, 2022)

Dietary nitrate does not acutely enhance skeletal muscle blood flow and vasodilation in the lower limbs of older adults during single-limb exercise - William E. Hughes; Nicholas T. Kruse; Kenichi Ueda; Andrew J. Feider; Satoshi Hanada; Joshua M. Bock; Darren P. Casey (European Journal of Applied Physiology, 2020)

Effect of gelling agent on colony formation in solid cultivation of microbial community in lake sediment - Hideyuki Tamaki; Satoshi Hanada; Yuji Sekiguchi; Yasuhiro Tanaka; Yoichi Kamagata (Environmental Microbiology, 2009)
Summary Since Robert Koch and colleagues found agar to be an effective gelling agent over a century ago, the pure culture method using agar plates has long been a standard of microbiology. Agar is undoubtedly easy to handle and useful for culture of microorganisms, but recent discovery of the ubiquity of microorganisms that cannot be cultured on agar raises a question: is agar really the best agent? In this study, we investigated the effect of two gelling agents, agar and gellan gum, on colony formation of a diverse array of microorganisms (total 108 strains) newly isolated from freshwater sediments and a representative microorganism as a slow grower on agar medium, Gemmatimonas aurantiaca , to clarify (i) whether they can grow on both agar and gellan gum plates, and (ii) the difference in time required for colony formation between the two gelling agents. Interestingly, 22 of 108 isolates showed no ability to form any visible colonies on the agar medium but did so on the gellan gum medium, and showed low 16S rRNA gene sequence similarities to their closest species. The remaining 86 isolates grew on both agar and gellan gum, but 52 of them grew much faster on gellan gum than on agar. Moreover, gellan gum also significantly stimulated the colony formation of the representative slow‐growing microorganism G. aurantiaca . Our results demonstrate that the gelling agent is a crucial factor for the growth of bacteria on plate media, and that alternatives to agar will be very important for increasing the culturability of yet‐to‐be cultured microorganisms.

Pelotomaculum terephthalicum sp. nov. and Pelotomaculum isophthalicum sp. nov.: two anaerobic bacteria that degrade phthalate isomers in syntrophic association with hydrogenotrophic methanogens - Yan-Ling Qiu; Yuji Sekiguchi; Satoshi Hanada; Hiroyuki Imachi; I-Cheng Tseng; Sheng-Shung Cheng; Akiyoshi Ohashi; Hideki Harada; Yoichi Kamagata (Archives of Microbiology, 2006)

Microbial community in a geothermal aquifer associated with the subsurface of the Great Artesian Basin, Australia - Hiroyuki Kimura; Maki Sugihara; Hiroyuki Yamamoto; Bharat K. C. Patel; Kenji Kato; Satoshi Hanada (Extremophiles, 2005)

A novel lineage of sulfate-reducing microorganisms: Thermodesulfobiaceae fam. nov., Thermodesulfobium narugense , gen. nov., sp. nov., a new thermophilic isolate from a hot spring - Koji Mori; Hongik Kim; Takeshi Kakegawa; Satoshi Hanada (Extremophiles, 2003)

Alkane-1,2-diol-based glycosides and fatty glycosides and wax esters in Roseiflexus castenholzii and hot spring microbial mats - Marcel van der Meer; Stefan Schouten; Satoshi Hanada; Ellen Hopmans; Jaap Damsté; David Ward (Archives of Microbiology, 2002)

Dihydroxylycopene diglucoside diesters: a novel class of carotenoids from the phototrophic purple sulfur bacteria Halorhodospira abdelmalekii and Halorhodospira halochloris - Shinichi Takaichi; Takashi Maoka; Satoshi Hanada; Johannes F. Imhoff (Archives of Microbiology, 2001)